miRNAs in the Diagnosis and Prognosis of Skin Cancer - Neagu, Monica; Constantin, Carolina; Cretoiu, Sanda Maria; Zurac, Sabina (Frontiers in Cell and Developmental Biology, 2020)
Skin cancer is at present the most common type of malignancy in the Caucasian population. Its incidence has increased rapidly in the last decade for both melanoma and non-melanoma skin cancer. Differential expression profiles of microRNAs (miRNAs) have been reported for a variety of different cancers, including skin cancers. Since miRNAs discovery as regulators of gene expression, their importance grew in the field of oncology. miRNAs can post-transcriptionally regulate gene expression, tumour initiation, development progression and aggressiveness. Nowadays, these short regulatory RNAs, are perceived as one of the epigenetic markers for identification of new diagnostic and/or prognostic molecular markers. Moreover, as miRNAs can drive tumorigenesis, they might eventually represent new therapy targets. Some miRNAs are pleiotropic like, miRNA-214 found deregulated in several other tumours besides skin cancers. Some others are specific for one or more skin cancer types, like miRNA-21 and miRNA-221 for cutaneous melanoma and cutaneous squamous carcinoma, or miRNA-155 for melanoma and cutaneous lymphoma. The goal of this review is to summarize some of the main miRNA detection technologies that are used to evaluate miRNA in tissues and body fluids. Furthermore, their quantification limits, conformity and robustness are discussed. Aberrant miRNA expression is analyzed for cutaneous melanoma, cutaneous squamous cell carcinoma, skin lymphomas, cutaneous lymphoma, and Merkel cell carcinoma. In this type of disease, miRNAs are described as potential biomarkers to diagnose early lesion and/or early metastatic disease. In the future, whether in tissue or circulating in body fluids, miRNAs will gain their place in skin cancer diagnosis, prognosis and future therapeutic targets.